Arachnoid cysts in childhood with endocrinological outcomes - Önal, Hasan; Adal, Erdal; Ersen, Atilla; Işık, Olcay; Onal, Zerrin; Arslan, Gülseren (The Turkish Journal of Pediatrics, 2011)
Arachnoid cysts are mainly manifested with the consequent neurological disorders. Even though these cysts may interfere in many systems due to their localizations, there is little information concerning their involvement in endocrinological disorders. We emphasize endocrinological functions together with cyst localizations and neurological disorders in childhood. A total of 50 patients diagnosed with arachnoid cysts were screened for cyst localizations, neurological symptoms and endocrinological outcomes evaluated by pubertal and growth status and hypothalamopituitary insufficiency. We investigated the interactions of these parameters. Arachnoid cysts were localized mostly in the middle fossa (54%) and posterior fossa (26%). Middle fossa cysts had a strong predilection for male gender (66.7% male) and left hemispheric dominancy (77%). We detected growth hormone deficiency in six patients, obesity in six patients and central precocious puberty in one patient; cysts were in the temporal area in three of the obese cases. All patients in our study had normal levels of cortisol, thyroid hormones and prolactin. In pediatric patients with arachnoid cysts, endocrinological follow-up is crucial as neurological outcomes and further evaluations are needed, mainly to confirm pubertal and growth status.